Factors of Development of the Management of the Design Education in Latvia - Irbite, Andra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The author proceeds with the discussion of significant problems in design industry and education in Europe and Latvia. This research is devoted to several important aspects in the development of design education in Latvia. Design education which is mainly based on the meaning of design as an aesthetic component of products, environment or communication, includes only a narrow range of specializations in the traditional fields of design. This concept affects the structure of design education and an beliefs of the areas in which designers will be able to work. Insufficiency of public awareness and understanding of the essence of design results in limited demand of design products and services. These factors determine the contribution of design sector to the economy and well-being of the society, as well as sensitivity of the labor force to market movements. In the research, by analyzing complex situation in the design branch and design education in Latvia, the author has developed proposals for the development of design education management.